Uso de recursos multimedia para la enseñanza aprendizaje del idioma kichwa en la UECIB Rumiñahui, en el periodo lectivo 2023 – 2024. - Guamán Puchaicela, Inti Pachacutic (2024)
Multimedia resources are effective tools in the teaching-learning process, as they integrate different types of content such as text, audio, video, and images, facilitating meaningful learning. For this reason, the present research, titled "The Use of Multimedia Resources for Teaching and Learning the Kichwa Language at UECIB Rumiñahui during the 2023–2024 Academic Year," was developed. The general objective was to analyze the use of multimedia resources in the teaching-learning process of the Kichwa language for the Básica Superior level at UECIB Rumiñahui, located in the town of San Lucas, Loja canton and province, during the period from August to October 2024. The specific objectives were to examine the theoretical foundations of multimedia resources and their relationship in the teaching-learning process of the Kichwa language, to establish the relationship between the use of multimedia resources and the teaching-learning of the Kichwa language, and to propose a didactic strategy for teaching and learning the Kichwa language through the interpretation of songs on the TikTok platform. In this research process, scientific, descriptive, inductive, deductive, and synthetic-analytic methods were used, with a mixed approach, making it a descriptive, explanatory, and correlational investigation. The techniques used included a survey, through its instrument, a questionnaire, applied to 35 students and 8 teachers from eighth to tenth grade, an interview employed to the institution's director, and an observation guide applied to the subject teacher. The achievement of the research allowed us to affirm that the use of multimedia resources is an effective method in the teaching-learning process of the language, strengthening the linguistic richness of Kichwa, both for teachers and students, and enabling us to propose a didactic strategy involving the use of these resources and their integration into digital platforms. Keywords: multimedia resources, teaching-learning, Kichwa language.